Efficacy of a single application of a new natural lice removal product. Preliminary data. - Scanni, G.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2006)
In a previous report most subjects treated with lice removal products and daily using combs able to remove nits recovered within four days from the first application of pediculicides. In this preliminary open study we applied only once in 5 children a natural pediculicide spray consisting of coconut oil extract, anise essential oil and Ylang ylang oil (Paranix®, Chefaro Pharma, Italy). Viable elements were not shown in any case after 7 days, thus making further applications of the product unnecessary.